ChemInform Abstract: Chiral Phosphorus‐Olefin Ligands for the RhI‐Catalyzed Asymmetric Addition of Aryl Boronic Acids to Electron‐Deficient Olefins. Issue 40 (September 2016) - Chen, Qian; Li, Liang; Zhou, Guangli; Ma, Xiaoli; Zhang, Lu; Guo, Fang; Luo, Yi; Xia, Wujiong
Abstract: The developed ligands allow for an efficient, highly enantioselective transformation of cyclic and acyclic α, β‐unsaturated carbonyl compounds according to the title reaction.